Analisis Alih Wahana Alternative Universe karya @ijoscriots ke dalam Novel Hilmy Milan karya Nadia Ristivani - Harahap, Dinar Hasanah; Setiadi, David (Peneliti.net, 2023)
Transfer of vehicles is the transfer of one type of work to another. Examples of this movement from novels to films are usually referred to as ecranization, or other movements such as from poetic texts to songs. This study analyzes the transfer process that occurs in an Alternative Universe work by Hilmy Milan (AU) into a novel. The AU object used in this study is the AU story by @ijoscripts which was transformed into the Hilmy Milan novel by Nadia Ristivani. The purpose of this study is to find out the process of analysis of vehicle transfer in the form of shrinkage that occurs when AU's work is transformed into a novel. This study used a descriptive qualitative method with data in the form of AU by @ijoscripts which was published on Twitter and the novel Hilmy Milan by Nadia Ristivani. This study obtained results in the form of attenuation related to the intrinsic elements of the theme and point of view. This shrinking obtained as many as three data on theme events and one data on the intrinsic elements of the point of view.